Analisis Keterampilan Bertanya Mahasiswa pada Mata Kuliah Strategi Pembelajaran Pendidikan Agama Islam di IAIN Manado - Yunus Nur Hidayat; Dwi Ratnasari; Nurul Fajriani Mokodompit (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2023)
The emergence of a knowledge always begins with a question. Students have good questioning skills which are one of the benchmarks for gathering information, informing what is known, and directing what is not known. The purpose of this study was to determine the impact of lecturer policies on the quantity and quality of students' ability to ask questions based on Bloom's taxonomy which has been revised in the course of Islamic Religious Education Material Development course. The method in this research is descriptive qualitative method. This research was conducted at FTIK IAIN Manado with the research respondents being all 5th semester C grade students, totaling 33 students. Based on the data obtained, it shows that the number of students who asked questions was 96%. The quality of the questions in this study was 40.62% in the category of low-level questions and 59.3% indicated that students asked questions in the high-level question category. Based on these results, it can be concluded that the student's ability to ask questions is classified as high, seeing from the most data, although not significant, so it is felt that it needs to be improved and developed.